A Cross-Sectional Study of Stress and the Perceived Style of Decision-Making in Clinicians and Patients With Cancer. (12th June 2019) - Vivian, Elaina; Oduor, Hellen; Lundberg, Laurie; Vo, Allison; Mantry, Parvez S
Background and Aims: Perceived stress and mindfulness can impact medical decision-making in both patients and clinicians. The aim of this study was to conduct a cross-sectional evaluation of the relationships between stress, mindfulness, self-regulation, perceptions of treatment conversations, and decision-making preferences among clinicians. Also, perceptions of treatment conversations and decision-making preferences among patients with cancer were evaluated. Methodology: Survey instruments were developed for clinicians and patients incorporating previously published questions and validated instruments. Institutional review board approval was obtained. Patients, physicians, and advanced practice providers from a tertiary referral center were asked to complete surveys. Continuous variables were evaluated for normality and then bivariate relationships between variables were evaluated using χ 2, Fisher's exact test, Cochran-Mantel-Haenszel (CMH) row mean scores differ statistic, or Kruskal-Wallis tests, where appropriate. Significance was defined at P < . 05. All tests were conducted using SAS v.9.4. Results: 77 patients and 86 clinicians (60.1% and 43% response rates, respectively) participated in the surveys. More clinicians who reported feeling "great/good" said they always/sometimes had enough time to spend with patients (66.1%) compared to those that hardly ever/never had enough time (26.3%), χ 2 (1, N = 75) = 6.62, P = .0101; CMH row mean scores differ statistic). Interestingly, 40.3% of patients preferred a paternalistic style of decision-making compared to 6.3% of clinicians, χ 2 (2, N = 146) = 27.46, P < .0001; χ 2 test. Higher levels of dispositional mindfulness (Mindful Attention Awareness Scale) were found among clinicians who reported they felt "great/good" (median = 4.5) as compared to those who reported that they were "definitely stressed/stressed out" (3.3), χ 2 (2, N = 80) = 10.32, P = .0057; Kruskal-Wallis test. Higher levels of emotional self-regulation (Emotional Regulation Questionnaire—Cognitive Reappraisal facet) were found among clinicians who reported they felt "great/good" (median = 31.0) compared to those who reported that they were "definitely stressed/stressed out" (20.0), χ 2 (2, N = 79) = 8.88, P = .0118; Kruskal-Wallis test. Conclusion: In order to have meaningful conversations about treatment planning, an understanding of mental well-being and its relationship to decision-making preferences is crucial for both oncology patients and clinicians. Our results show that for clinicians, lower perceived stress was associated with higher levels of mindfulness (experiencing the present moment), emotional self-regulation, and spending more time with patients. Larger prospective studies are needed to validate these findings.